Analisis Gender terhadap Preferensi Ibu Rumah Tangga sebagai Penerima Program Keluarga Harapan - Mella Putri Ayuningtyas; Zulkipli Lessy (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to explain why the Family Hope Program (PKH) specifically targets housewives as beneficiaries, as well as to describe the empowerment efforts carried out by PKH Kapanewon Jetis Yogyakarta. Data collection methods used were interviews and relevant previous research, with descriptive qualitative analysis. The results showed that PKH Kapanewon Jetis Yogyakarta not only contributed social funds, but also empowered people in various aspects such as health counseling for pregnant women, empowering MSMEs, and educational counseling. Until now, this program has empowered nearly 4,000 Beneficiary Families (KPM) spread across four sub-districts. Empowerment is carried out through the division of KPM into groups in each sub-district. The main beneficiaries are adult women, because their roles and responsibilities within the household are considered more targeted. This approach is in accordance with Presidential Instruction (Inpres) Number 9 of 2000 concerning Gender Mainstreaming which emphasizes equal rights of women and men in various aspects of life.